A new carbon allotrope: Penta-graphene as a metal-free catalyst for CO oxidation. (April 2017) - Krishnan, Ranganathan; Su, Wan-Sheng; Chen, Hsin-Tsung
Abstract: We performed first-principles calculations to study CO oxidation on a new carbon allotrope called penta-graphene (PG). The CO oxidation involves CO + O2  → CO2  + O and CO + O → CO2 reactions considering through Eley–Rideal (ER) and Langmuir–Hinshelwood (LH) mechanisms. The ER mechanism proceeds the oxidization of CO to CO2 by the pre-adsorbed O2 on the PG sheet. The energy barrier is predicted to be 0.65 eV. The LH mechanism takes place by co-adsorbed CO and O2 on PG sheet with an energy barrier as low as 0.31 eV. These predicted values are quite close to those processes catalyzed by noble metals. In addition, we analyzed the LDOS at each step of ER and LH mechanisms to deeply understand the catalytic properties of PG. Our calculation results illustrate that PG is a potential, metal-free, and low-cost catalyst for low-temperature CO oxidation. This study contributes to designing more effective carbon allotrope catalysts and widening the applications of carbon allotrope. Graphical abstract: We performed first-principles calculations to study CO oxidation on a new carbon allotrope called penta-graphene (PG). The CO oxidation involves CO + O2  → CO2  + O and CO + O → CO2 reactions considering through Eley–Rideal (ER) and Langmuir–Hinshelwood (LH) mechanisms.